Is Addenbrooke's Cognitive Examination III Sensitive Enough to Detect Cognitive Dysfunctions in Patients with Focal Cerebellar Lesions?. (14th June 2021) - Starowicz-Filip, Anna; Prochwicz, Katarzyna; Kłosowska, Joanna; Chrobak, Adrian Andrzej; Krzyżewski, Roger; Myszka, Aneta; Rajtar-Zembaty, Anna; Bętkowska-Korpała, Barbara; Kwinta, Borys
Abstract: Objective: The main aim of the study was to evaluate whether the available brief test of mental functions Addenbrooke's cognitive examination III (ACE III) detects cognitive impairment in patients with cerebellar damage. The second goal was to show the ACE III cognitive impairment profile of patients with focal cerebellar lesions. Method: The study sample consisted of 31 patients with focal cerebellar lesions, 78 patients with supratentorial brain damage, and 31 subjects after spine surgery or with spine degeneration considered as control group, free of organic brain damage. The ACE III was used. Results: Patients with cerebellar damage obtained significantly lower results in the ACE III total score and in several subscales: attention, fluency, language, and visuospatial domains than healthy controls without brain damage. With the cut-off level of 89 points, the ACE III was characterized by the sensitivity of 71%, specificity of 72%, and accuracy of 72%. The cerebellar cognitive impairment profile was found to be "frontal-like" and similar to that observed in patients with anterior supratentorial brain damage, with decreased ability to retrieve previously learned material and its preserved recognition, impaired word fluency, and executive dysfunction. The results are consistent with cerebellar cognitive affective syndrome. Conclusions: The ACE III can be used as a sensitive screening tool to detect cognitive impairments in patients with cerebellar damage.